2020
DOI: 10.3889/oamjms.2020.4714
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Children: A Narrative Review

Abstract: BACKGROUND: In December 2019, coronavirus (CoV) disease 2019 (COVID-19) was detected in Wuhan, China, which is known as severe acute respiratory syndrome CoV 2 (Severe acute respiratory syndrome [SARS]-CoV-2). AIM: This study attempted a narrative review of the researches about COVID-19 in children. METHODS: We searched all articles between 2000 and April 2020 in PubMed, Scopus, and ScienceDirect related to COVID-19 in children, using the following terms: “COVID-19,” “coronavirus,” “SARS-CoV-2” in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
(111 reference statements)
0
9
0
Order By: Relevance
“…This is in agreement with studies which showed elevation of D-dimer to some extent, especially those with severe disease (LDH and D-dimer) [ 8 , 48 ]. Razavi et al [ 49 ] found elevation of CRP, ESR and D-dimer in children with severe manifestations. Momtazmanesh et al [ 50 ] reported elevation of ESR and CRP 71.8 and 75.4% and elevation of LDH and D-dimer in 40% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with studies which showed elevation of D-dimer to some extent, especially those with severe disease (LDH and D-dimer) [ 8 , 48 ]. Razavi et al [ 49 ] found elevation of CRP, ESR and D-dimer in children with severe manifestations. Momtazmanesh et al [ 50 ] reported elevation of ESR and CRP 71.8 and 75.4% and elevation of LDH and D-dimer in 40% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In December 2019, COVID-19 was detected in Wuhan, China. It has a very high transmission capacity and is known as SARS-CoV-2 [2]. COVID-19 is highly contagious and it has the ability to get transmitted even during asymptomatic phase.…”
Section: Introductionmentioning
confidence: 99%
“…In December 2019, unknown pneumonia was reported in Wuhan, China, which belongs to the coronavirus family (1, 2). The most important way of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission is through direct person-to-person contact and respiratory droplets (3). In addition, this virus was also detected in urine, feces, and tears, which confirm the possibility of transmission through the fecal-oral route (4, 5).…”
Section: Introductionmentioning
confidence: 99%